Assistance for Micro Entrepreneurs to Obtain Halal Certification from SEHATI 2022 - Hidayati, Irma (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research examines the challenges faced by MSMEs in Indonesia when obtaining halal certification through the SEHATI 2022 program. It focuses on obstacles like the complexity of procedures and lack of awareness about the program and SIHALAL system, impacting micro-businesses' ability to secure halal certification.Method: The study uses qualitative methods, including interviews with halal facilitators and MSMEs, and document analysis related to the SEHATI 2022 program. Thematic analysis was applied to identify challenges in understanding and using the SIHALAL system.Practical Applications: The findings highlight ways to simplify the halal certification process for MSMEs, emphasizing the need to increase awareness and improve the role of halal facilitators. This can help more businesses benefit from SEHATI 2022 and enhance market opportunities for halal-certified products.Conclusion: While SEHATI 2022 offers financial support, complex procedures and low awareness hinder MSMEs. Strengthening facilitation and simplifying the SIHALAL system are crucial for improving halal certification access for micro-entrepreneurs.